Rediscovery of the rare Andean blindsnake Anomalepis colombia Marx 1953 (Serpentes: Anomalepididae) in the wild - Vanegas-Guerrero, Jhonattan; Martins, Angele; Quiñones-Betancurt, Esteban; Lynch, John D. (Zootaxa, 2019)
The fossorial snake genus Anomalepis Jan 1860 currently comprises four species with distribution restricted to the Neotropics, occurring from Nicaragua to trans-Andean Peru. Species of Anomalepis occur on the mainland from sea level to about 2,700 m elevation in habitats that range from xerophyte vegetation to tropical wet forests (Kofron 1988; McDiarmid et al. 1999; Uetz et al. 2019; Wallach et al. 2014). Kofron (1988) performed a taxonomic review of the genus Anomalepis, recognizing two phenotypic clusters of species: the A. mexicanus Jan 1860 composed exclusively by its nominal form, and the A. aspinosus Taylor 1939 group consisting of the former species, A. colombia Marx 1953 (Fig. 1) and A. flavapices Peters 1957. While Anomalepis aspinosus occurs in xerophytic formation from 500–2700 above sea level (asl hereafter) along the Peruvian Andes (Kofron 1988; McDiarmid et al. 1999; Wallach et al. 2014), and Anomalepis flavapices is found in the coastal rainforest plains of northwestern Ecuador (Kofron 1988; Wallach et al. 2014), Anomalepis mexicanus presents the most widespread distribution amongst its congeners, occurring in northeastern Honduras, Nicaragua, Costa Rica and Panama from sea level to 725 m altitude. Even though this species has previously been recorded for Peru (Kofron, 1988), it seems unlikely that this specimen belongs to A. mexicanus due to its distinct meristic features (see Kofron 1988) and its outlandish record (see Fig. 2). Marx (1953) described Anomalepis colombia based on a single specimen collected in 1946 by Kjell von Sneidern at La Selva (05º25’23N, 74º57’44W; 1700 m asl), municipality of Pueblo Rico, department of Caldas, Colombia. As far as we know, since its original description, no additional specimen of A. colombia has been reported in literature (cf. Kofron 1988; McDiarmid et al. 1999; Wallach et al. 2014).